Guidance impulse algorithms for air bomb control - Glebocki, R (Bulletin of the Polish Academy of Sciences. Technical sciences, 2012)
In this paper, some results of research concerning the development of guidance of bombs were presented. The paper presents conceptions of an impulse (gasodynamic) control system, the measurement unit based on IMU/GPS signals and control algorithms based on predicted trajectories. The presented results of simulation research are based on the numerical model of the bomb and real signals from measurement devices.